2017
DOI: 10.1016/j.jana.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Longitudinal Mentorship to Strengthen the HIV Workforce: Qualitative Evidence of Changes in Clinicians' Knowledge, Attitudes, and Practice

Abstract: The Clinician Scholars Program at the Midwest AIDS Training and Education Center strengthens the workforce by increasing knowledge and skills related to HIV prevention and care. The 1-year individualized training program for minority-serving clinicians includes intensive mentoring and networking. Qualitative exit interviews (N = 50) conducted over 4 years demonstrate the effectiveness of the training, including changes at the individual and systems levels. Findings show that almost all graduates reported impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…To achieve these results, a "team of teams" approach, with solutions derived not from a hierarchical dictatorship, but rather from more complex multi-directional relationships, were critical to program success. More experienced public health managers at CDC and MOH provided onsite and remote sessions on evidence-based innovations to mentors who in turn provided context to the strategies and mentorship to facility staff 4,14,15 . Key aspects of Zambia's national HIV clinical mentorship program were that it was government led, which ensured authority and sustainability; incorporated video-conferencing technology, which enabled mentors to interact with mentees on a regular basis, and that there was a commitment to a continuous quality improvement methodology, which led to innovation and improvement, rather than just performance monitoring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve these results, a "team of teams" approach, with solutions derived not from a hierarchical dictatorship, but rather from more complex multi-directional relationships, were critical to program success. More experienced public health managers at CDC and MOH provided onsite and remote sessions on evidence-based innovations to mentors who in turn provided context to the strategies and mentorship to facility staff 4,14,15 . Key aspects of Zambia's national HIV clinical mentorship program were that it was government led, which ensured authority and sustainability; incorporated video-conferencing technology, which enabled mentors to interact with mentees on a regular basis, and that there was a commitment to a continuous quality improvement methodology, which led to innovation and improvement, rather than just performance monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…This is compounded by the reality that specialist care is more often concentrated in urban areas, far out of the reach of much of Zambia's population. In the United States and Sub-Saharan Africa, HIV clinical mentorship has been shown to improve clinical practices and outcomes related to linking and retaining patients in HIV care and across varying disciplines 4,5,6,7 . Furthermore, in resource limited settings where distance is a barrier to providing ongoing clinical training and mentorship, Project ECHO (Extension for Community Healthcare Outcomes), which uses video-conferencing technology to bridge knowledge gaps between experts and providers, has demonstrated an impact on patient outcomes 8,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these results, a "team of teams" approach, with solutions derived not from a hierarchical dictatorship, but rather from more complex multi-directional relationships, were critical to program success [14]. More experienced public health managers at CDC and Ministry of Health provided onsite and remote sessions on evidence-based innovations to mentors who in turn provided context to the strategies and mentorship to facility staff [4,14,15]. Key aspects of Zambia's national HIV clinical mentorship program were that it was government led, which ensured authority and sustainability; incorporated video-conferencing technology, which enabled mentors to interact with mentees on a regular basis, and that there was a commitment to a continuous quality improvement methodology, which led to innovation and improvement, rather than just performance monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…This is compounded by the reality that specialist care is more often concentrated in urban areas, far out of the reach of much of Zambia's population. In the United States, Canada and Uganda, HIV clinical mentorship has been shown to improve clinical practices and outcomes related to linking and retaining patients in HIV care and across varying disciplines [4][5][6][7]. Furthermore, in resource limited settings where distance is a barrier to providing ongoing clinical training and mentorship, Project ECHO (Extension for Community Healthcare Outcomes), which uses video-conferencing technology to bridge knowledge gaps between experts and providers, has demonstrated an impact on patient outcomes [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging PrEP literature also supports customized training; recent studies indicated the need for (1) tailoring training to provider needs [ 38 ] and (2) provider preferences regarding PrEP training content and format depending on clinical experience [ 8 , 33 ]. Other studies have shown clinician mentoring programs to be successful training models to bolster the HIV workforce [ 39 , 40 ]. Although various PrEP training formats exist, our findings support utilizing provider-, clinic-, and county-level characteristics and CFIR-guided assessments to shape trainings for specific audiences [ 33 , 41 ].…”
Section: Discussionmentioning
confidence: 99%